The role of HSP 70 in the implementation of neuroprotective effect of (s)-2,6-diaminogexane acid 3-methyl-1,2,4-triasolile-5-tyoacetate (angiolyne) in deprivation of the system`s level of restored glutathione in vitro - Belenichev, I. F.; Kucherenko, L. I.; Aliyeva, O. H.; Skorina, D. Yu.; Бєленічев, Ігор Федорович; Кучеренко, Людмила Іванівна; Алієва, Олена Геннадіївна; Скорина, Дмитро Юрійович (Запорізький державний медичний університет, 2022)
The aim of the research: to determine the value of the heat shock protein HSP70 in the implementation of the mechanism of neuroprotective actions of substance with neuroprotection, endothelioprotection, antioxidant activity -(S)-2,6-diaminogexane acid 3-methyl-1,2,4-triasolile-5-tyoacetate.
Keywords: тези доповідей